Is VMAT beneficial for patients undergoing radiotherapy to the head and neck?. Issue 1 (February 2017) - Osborn, J.
Abstract: Volumetric Intensity-Modulated Arc Therapy (VMAT) offers solutions to the time consuming, higher monitor unit (MU) delivery of Intensity-Modulated Radiotherapy (IMRT) for patients undergoing radiotherapy for head and neck cancer (HNC). Thus the aim was to determine whether VMAT would be beneficial for these patients. The majority of literature was planning comparative studies with only two studies on early clinical experience. Main themes arising from literature were conformity and homogeneity, organs at risk (OAR), MU and delivery time. VMAT provides plans with similar conformity, better homogeneity and results for improved sparing of OAR compared to IMRT. Thus it is clear that VMAT would be able to match the performance of IMRT plans, with the ability to treat patients in a short space of time and less MU. There is little clinical data on the side effects of VMAT, and more is needed to further evaluate the efficacy of VMAT. Overall these are encouraging results of VMAT for patients with HNC. Highlights: VMAT offers solutions to the time consuming, higher MU delivery of IMRT for patients with HNC. Two arc VMAT plans provide similar conformity and better homogeneity than IMRT plans. VMAT provides encouraging results for improved sparing of OAR compared to IMRT. Due to VMAT being a new technique there is little clinical data on the toxicities.